De novo assembly and annotation of the pantranscriptome of Astyanax lacustris on the liver and pituitary-gonadal axis - Aciole Barbosa, David; Branco, Giovana Souza; Dal'Olio Gomes, Aline [UNESP]; Tolussi, Carlos Eduardo; Muñoz-Peñuela, Marcela; Araújo, Bruno C.; da Silva, Iuri Batista; Moreira, Renata Guimarães; Nunes, Luiz R.; Menegidio, Fabiano B. (Elsevier, 2025)
Astyanax lacustris is a model of laboratory native fish species. Reproductive studies of this species have already been performed. Nevertheless, there is a relative shortcoming of gene sequence information available in public databases, which hinder their use in more comprehensive investigations that employ sensitivity molecular biology techniques to assess gene expression profile for biomarker identification. In this data article, we report the first de novo transcriptome assembly of A. lacustris testicles, ovaries and male / female pituitary gland improving gene sequence data available for this fish species and transcriptome of male liver. Illumina sequencing generated 808,023,356 raw reads, filtered in 752,739,866 high-quality reads. Initially, a de novo assembly was filtered to include protein coding elements only in each tissue sample, which were merged in a final pantranscriptome (PAN) containing 109,232 contigs. The PAN was functionally annotated against a custom Actinopterygii proteins dataset and EggNOG terms with the aid of EnTAP, retrieving homology queries for about 90 % of all transcripts. Therefore, in this study we provide a PAN and a custom blast tool that can help discovery genomic information on metabolism pathways and their related genes in A. lacustris, enabling future research and molecular studies using this fish species as a model.
Keywords: Hepatic; Ovaries; Pituitary; Reproduction; RNAseq; Testis